The impact of market system development approaches: The case of InovAgro in Mozambique - Amare, Mulubrhan; Zavale, Helder; Smart, Jenny; Ghebru, Hosaena (International Food Policy Research Institute, 2022)
Market system development (MSD) approaches aim to address market failures and frictions that frequently impede adoption of modern yield-enhancing agricultural practices in sub-Saharah Africa. This brief examines the impact of an MSD intervention (InovAgro) in Mozambique that was designed to increase incomes and improve economic security for poor smallholder farmers through improved productivity and development of high-potential value chains. Findings include increases in use of inputs and access to market information, as well as important spillover effects for many small-scale farmers beyond the direct beneficiaries, and high costs-effectiveness of the MSD intervention.